URGENSI IMPELEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENANAMKAN NILAI-NILAI KARAKTER DI SEKOLAH - ABDULLAH K (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2019)
Abstract: Many students' behaviors that are not in accordance with the noble values of the nation, for example, attitudes only selfish, breaking the law, deviant behavior among students and students who tend to increase, even brawl in congregation, bullying, acts of immorality, fornography, drug addicts, cheating, plagiarism and liquor became the hot news adorning the media all the time. so that it becomes the talk of various parties who show concern for the importance of improving the character of students. It seems to have lost the character that has been built for centuries, such as friendliness, social solidarity and helpfulness. Educational institutions are considered not optimal in shaping the personality of students, thus inspiring the emergence of a commitment to boost character education in an integrated and tiered manner, which requires school-based management in its implementation. Keywords: School based management, building up character value.